2023
DOI: 10.1111/tgis.13098
|View full text |Cite
|
Sign up to set email alerts
|

Modelling underground cadastral survey data in CityGML

Bahram Saeidian,
Abbas Rajabifard,
Behnam Atazadeh
et al.

Abstract: In underground environments, survey elements such as survey points and observations provide the information required to define legal boundaries. These elements are also used to connect underground legal spaces to a geodetic survey network. Due to the issues of current 2D approaches for managing underground cadastral data, prominent 3D data models have been extended to support underground land administration. However, previous studies mostly focused on defining underground legal spaces and boundaries, with less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A 3D cadastral data model should meet all the legal, physical, and relationship requirements including multidimensional data and their topological relationships, dynamic data, complex and irregular shapes, and so on. Assigning property boundaries to physical objects highly depends on the spatial integrity of the model and adopted design methods [3]. Moreover, to ensure that the database designed meets all of the associated requirements, a guarantee must also be provided [30].…”
Section: Challenges Of Conceptual Design and Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3D cadastral data model should meet all the legal, physical, and relationship requirements including multidimensional data and their topological relationships, dynamic data, complex and irregular shapes, and so on. Assigning property boundaries to physical objects highly depends on the spatial integrity of the model and adopted design methods [3]. Moreover, to ensure that the database designed meets all of the associated requirements, a guarantee must also be provided [30].…”
Section: Challenges Of Conceptual Design and Standardsmentioning
confidence: 99%
“…A cadastral data model is required to cover both legal and physical aspects, as well as survey elements [3,4], which contains spatial and non-spatial data [5], multi-purpose and multidimensional data including 0D-4D (3D + time) [6][7][8][9], 5D (4D + scale [10] or 3D + bi-temporal [11]), metadata, and observations and measurements [12]. It is also suggested that the Land Administration Domain Model (LADM) should be expanded to include marine, valuation, and spatial plan information [13,14].…”
Section: Introductionmentioning
confidence: 99%